Dyspareunia is rarely assessed in rodent models of endometriosis and interstitial cystitis/bladder pain syndrome - Paulina Nunez-Badinez; Razneen Shah; Lysia Demetriou; Bianca De Leo; Jane Meijlink; Judy Birch; Nicole Schmidt; Jens Nagel; Katy Vincent (Reproduction and Fertility)
Dyspareunia, or pain during sex, is a common and often debilitating symptom in individuals with endometriosis and/or interstitial cystitis/bladder pain syndrome (IC/BPS). Despite its significant impact on quality of life, it is frequently overlooked in research. This review evaluates how dyspareunia has been addressed in preclinical investigations of these conditions. A systematic search was conducted using Embase from 1998 to 2021, identifying original in vivo preclinical studies using female rodents to model (i) endometriosis and (ii) IC/BPS. The search aimed to identify studies that assessed dyspareunia. Study quality and risk of bias were evaluated using a modified CAMARADES checklist. Our analysis found 1,286 studies modelling endometriosis and 674 modelling IC/BPS, but only 18 and 1, respectively, measured dyspareunia. The most common method involved vaginal distention in rats, assessed by either behavioural escape responses or visceromotor reflexes of abdominal muscles. Despite the high prevalence of dyspareunia in these conditions, it is rarely measured in preclinical studies. We identify a significant gap in the literature and offer succinct recommendations for future translational research to address this important symptom.